The Impact of a Website-Based Village Information System on Public Services (Research at the North Pangulah Village Office) - Taruna Nugraha; Risma Fitriani; Dene Herwanto (International Journal of Science and Environment (IJSE), 2026)
The majority of residents in Pangulah Utara Village have not yet optimally utilized the web-based village service information system. The primary obstacle is a limitation in human resources—particularly among the 40-to-60 age group—who still struggle with using the internet. This study aims to examine the web-based Village Information System (SID) in Pangulah Utara Village, Karawang Regency; to assess the effectiveness of public services utilizing the Population Administration Information System in the village; and to determine the impact of the web-based Village Information System on public service effectiveness in the area. The study employs a quantitative survey method, utilizing questionnaires to collect data from a sample of 500 individuals. Data analysis techniques include instrument testing (validity and reliability), normality testing, correlation analysis, and hypothesis testing (simple linear regression and coefficient of determination analysis). The results of the simple linear regression analysis regarding the web-based Information System and public services in Pangulah Utara Village—based on data from 84 participants across five indicators (information availability, ease of use, access speed, system security, and interactive features/online services)—indicate a high level of performance, falling within the 3.40–4.19 interval range with a mean score of 4.07. Similarly, the effectiveness of public services in Pangulah Utara Village—assessed via 84 participants across four indicators (service satisfaction, process efficiency, accessibility and fairness, and transparency and accountability)—also falls into the high-performance category, situated within the 3.40–4.19 interval range with a mean score of 4.04. Regarding the influence of the web-based Village Information System on public services in Pangulah Utara Village, it is concluded that the system has a significant impact on service effectiveness, accounting for 96.8% of the effect, while the remainder is attributed to other factors not included in this study.